2017
DOI: 10.18632/oncotarget.18801
|View full text |Cite
|
Sign up to set email alerts
|

MiR-200c inhibits bladder cancer progression by targeting lactate dehydrogenase A

Abstract: Lactate dehydrogenase A (LDHA) is overexpressed in various cancers. We investigated LDHA expression and function in bladder cancer. We demonstrate that LDHA is up-regulated in bladder cancer cells and promotes proliferation, invasion, and glycolysis. Additionally, we found that microRNA (miR)-200c directly targets LDHA in bladder cancer cells. Ectopic expression of miR-200c inhibited LDHA-induced glycolysis, cell proliferation, and invasion. Thus, targeting LDHA through miR-200c is a potential therapeutic stra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
22
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 28 publications
0
22
0
Order By: Relevance
“…22 It has been shown that the expression of miRNA is changed in cancer via several mechanisms such as miRNA gene deletion or amplification. 25 Zhang et al 26 reported that miR-200c suppressed the breast cancer cell metastasis via downregulation of forkhead box F2 expression. Individual miRNAs can regulate multiple mRNAs, and several distinct miRNAs can suppress a single mRNA.…”
Section: Discussionmentioning
confidence: 99%
“…22 It has been shown that the expression of miRNA is changed in cancer via several mechanisms such as miRNA gene deletion or amplification. 25 Zhang et al 26 reported that miR-200c suppressed the breast cancer cell metastasis via downregulation of forkhead box F2 expression. Individual miRNAs can regulate multiple mRNAs, and several distinct miRNAs can suppress a single mRNA.…”
Section: Discussionmentioning
confidence: 99%
“…In this present study, knockdown of LDHA expression using LDHA targeting siRNA significantly suppressed the proliferation and migration of A549 and NCI-H460 NSCLC cells, similar to the effects observed following miR-200c overexpression. In addition, LDHA has been identified as a direct target of miR-200c in bladder cancer 29 . Therefore, the present study provides further evidence regarding the relationship between miR-200c and LDHA in human cancer.…”
Section: Discussionmentioning
confidence: 99%
“…MiR-200c is a well-known tumor suppressor, and its downregulation has been observed in various cancers, such as breast cancer, gastric cancer, etc [16,17]. In bladder cancer, it has been reported that the ectopic expression of miR-200c could inhibit bladder cancer cell proliferation and invasion in vitro [18]. MiR-200c may be involved in tumorigenesis of bladder cancer, which may be employed as an indicator for early screening of the malignant disease.…”
Section: Introductionmentioning
confidence: 99%